Demographic and clinical profile with early outcome of critically ill COVID-19 patients admitted in an ICU of a tertiary care hospital in Dhaka, Bangladesh (BIRDEM Medical Journal, 2020)
Background: First outbreak of corona virus disease (COVID-19) started in Wuhan, China at December 2019 and since then, it spread globally but information about critically ill patients with COVID-19 is still limited. So, it is important to know the demographic profile and overall outcome of COVID-19 patients. We aimed to describe the clinic-demographic characteristics and outcome of critically ill COVID-19 patients admitted in our intensive care unit.Methods: This prospective observational study was carried out in the intensive care unit of department of Critical Care Medicine of BIRDEM General Hospital, Dhaka, Bangladesh from 11th June to 31st October, 2020. Out of 382 suspected cases, 86 patients were found to be RT-PCR for COVID-19 positive and were included in this study. After admission in ICU, all patients were resuscitated according to ICU protocol. Length of ICU stay were recorded and patient outcomes were mentioned as survival (transferred or discharged) or death.Results: A total of 86 patients (male 53, female 33, mean age 63.6 ± 12.8 years) with RT-PCR for COVID-19 positive were enrolled in this study. Regarding COVID related symptoms, Ninety six percent(83) had respiratory distress, 93.02 % (n=80) had cough, 84.9% (n=73) had history of fever,11.6 % (n=10) had loose motion and 7% (n=6), had anosmia. Diabetes mellitus (DM) was the most common co morbidity (91.9%).For improvement of oxygenation of COVID patient, we treated 7% of patients (n=6) by nasal Cannula, 24.4% (n=21) by Face Mask, 20.9% (n=18) by Non Rebreather Mask, 22.1% (n= 19) by High Flow Nasal Cannula (HFNC) and 25.6% (n= 22) by Mechanical Ventilation. Mean length of ICU stay were 6.9 ± 3.6 days and range of icu stay were 1-20 days. Among 86 COVID patient, 51.16% (n=44) were transferred to the isolation ward or discharged at home and 48.8% (n=42) were died.Conclusion: This study showed the overall demographic and clinical features of critically ill COVID-19 patients, admitted in an icu of a tertiary care hospital. As it is a single centered study, we need more study with multi center approach to know the detail demographic profile and outcome of COVID-19 patients.Birdem Med J 2020; 10, COVID Supplement: 51-55